Delanzomib, a novel proteasome inhibitor, sensitizes breast cancer cells to doxorubicin‐induced apoptosis. Issue 4 (18th March 2019) - Wang, Mopei; Liang, Li; Lu, Jiaxiong; Yu, Yang; Zhao, Yanling; Shi, Zhenfeng; Li, Hui; Xu, Xin; Yan, Yuxian; Niu, Yan; Liu, Zhentao; Shen, Lin; et al.
Abstract : Background: Delanzomib, a novel proteasome inhibitor, has demonstrated promising efficacy and antitumor ability in human multiple myeloma cell lines and patient‐derived cells. However, the potential therapeutic effects of delanzomib on breast cancer remain unknown. In this study, we show that delanzomib has antitumor effects and synergizes with doxorubicin (Dox) in human breast cancer cell lines. Methods: Cell proliferation assay and flow cytometry were used to evaluate cell viability and apoptosis in eight human breast cancer cell lines after treatment with delanzomib or Dox. Essential molecules of the p53, MAPK, and apoptosis signaling pathways were analyzed by Western blotting. Results: Delanzomib induced cell death and demonstrated synergism with Dox in all tested breast cancer cell lines. In addition, delanzomib enhanced the Dox‐induced phosphorylation of p38/JNK and the expression of transcriptional target proteins of p53, such as p21, p27, NOXA, and PUMA. Conclusion: The combined regimen of the proteasome inhibitor delanzomib with Dox chemotherapy may become an effective strategy for breast cancer therapy.